Uncertainty estimation approach in catalytic fast pyrolysis of rice husk : Thermal degradation, kinetic and thermodynamic parameters study - Yiin, Chung Loong; Chun, Adrian Minh Loy; Suzana, Binti Yusup; Bing, Shen How; Lai, Bridgid Fui Chin; Mustakimah, Binti Muhammad; Yong, Ling Gwee (Elsevier Ltd., 2019)
The aim of this study was to understand the influence of catalyst in thermal degradation behavior of rice husk (RH) in catalytic fast pyrolysis (CFP) process. An iso-conversional Kissinger kinetic model was introduced into this study to understand the activation energy (EA), pre-exponential value (A), Enthalpy (ΔH), Entropy (ΔS) and Gibb’s energy (ΔG) of non-catalytic fast pyrolysis (NCFP) and CFP of RH. The study revealed that the addition of natural zeolite catalyst enhanced the rate of devolatilization and decomposition of RH associated with lowest EA value (153.10 kJ/mol) compared to other NCFP and CFP using nickel catalyst. Lastly, an uncertainty estimation was applied on the best fit non-linear regression model (MNLR) to identify the explanatory variables. The finding showed that it had the highest probability to obtain 73.8–74.0% mass loss in CFP of rice husk using natural zeolite catalyst.